2000
DOI: 10.1016/s0002-9440(10)64769-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Hybridization Reveals Frequent Losses of Chromosomes 1p and 3q in Pheochromocytomas and Abdominal Paragangliomas, Suggesting a Common Genetic Etiology

Abstract: Pheochromocytomas and abdominal paragangliomas are rare, catecholamine-producing tumors that arise from the chromaffin cells derived from the neural crest. We used comparative genomic hybridization (CGH) to screen for copy number changes in 23 pheochromocytomas and 11 abdominal paragangliomas. The pattern of copy number changes was similar between pheochromocytomas and paragangliomas, with the most consistent finding being loss of 1cen-p31, which was detected in 28/34 tumors (82%). Losses were also found on 3q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

20
93
2
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(119 citation statements)
references
References 28 publications
20
93
2
3
Order By: Relevance
“…The suppressor gene p73 on 1p 36 32 which in neuroblastomas is clearly associated with a poor prognosis 27 seems to be of lesser importance in PCC. 2 In this study, gains on 12q (6/0) and 20q (7/2) and losses of 9p (4/0) were found in 10-22% of all cases with a statistical predominance in metastasized tumors. However, these results are not strong enough to support a definite correlation and need to be confirmed by further investigations.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…The suppressor gene p73 on 1p 36 32 which in neuroblastomas is clearly associated with a poor prognosis 27 seems to be of lesser importance in PCC. 2 In this study, gains on 12q (6/0) and 20q (7/2) and losses of 9p (4/0) were found in 10-22% of all cases with a statistical predominance in metastasized tumors. However, these results are not strong enough to support a definite correlation and need to be confirmed by further investigations.…”
Section: Discussionsupporting
confidence: 46%
“…[2][3][4] In those studies, the number of malignant adrenal PCC investigated was low (four, respectively, 10 sporadic malignant adrenal PCC) and the PASS scale had not yet been introduced.…”
mentioning
confidence: 99%
“…A region of common deletion on chromosome 3 has been described in uveal melanomas at 3q24-26, 19 a site that is infrequently affected in most tumours but is deleted in osteosarcomas, paragangliomas, and pheochromocytomas. [26][27][28] An additional tumour with a deletion involving 3q25.1-ter has also been reported in a single case of uveal melanoma, consistent with this region harbouring a TSG. 25 Here we report the screening of 52 cases of uveal melanoma for partial deletions of chromosome 3, the findings of which confirm previously reported commonly deleted regions at 3p25 and 3p11-14.…”
Section: Discussionmentioning
confidence: 87%
“…The gain of 16p region in malignant pheochromocytomas has been previously described. 36 As the histological analysis of pheochromocytomas for the establishment of malignancy and for the prediction of tumor recurrence is unreliable, miR-1225-3p might be of clinical importance for selecting patients with potentially recurring pheochromocytomas. Patients harboring tumors overexpressing miR-1225-3p should be regularly screened.…”
Section: Discussionmentioning
confidence: 99%